Efficacy and compatibility mechanism of bear bile powder in Shexiang Tongxin dropping pills for acute myocardial infarction treatment - Yu Luo; Fangmin Zhang; Lidan Zhu; Jianfeng Ye; Hong-ye Pan; Xiaoyan Lu; Xiaohui Fan (Chinese Medicine)
Abstract Background Bear bile powder (BBP), a unique animal-derived medicine with anti-inflammatory and antioxidant effects, is used in Shexiang Tongxin dropping pills (STDP), which is applied to treat cardiovascular diseases, including acute myocardial infarction (AMI). The efficacy and compatibility mechanisms of action of BBP in STDP against cardiovascular diseases remain unclear. This study aimed to investigate the compatibility effects of BBP in STDP in rats with AMI. Methods We investigated the compatibility effects of BBP in STDP in rats with AMI. Non-targeted metabonomics, 16S rRNA analysis, RNA sequencing, and network pharmacology were performed to explore the underlying mechanisms. Results The combination of BBP and CF (STDP without BBP) significantly reduced AMI-induced infarction size, pathological alterations of cardiac tissues, and serum lactate dehydrogenase and creatine kinase levels in rats, compared with CF or BBP treatment alone. Gut microbiota and metabonomics results revealed that the combination treatment could upregulate the relative abundance of Lactobacillus and downregulate that of Helicobacter, Bilophila, and Butyricimonas, thereby rebalancing the gut microbiota dysbiosis induced by AMI. Consequently, the intestinal metabolite levels of oleoylcholine, glutamylalanine, isokobusone, and hemorphin-4 were altered. However, treatment with CF or BBP alone has a weaker effect on these bacteria. Additionally, the combination treatment induced a 62.34% gene reversion rate compared with 55.56% for BBP and 30.20% for CF treatment alone. Modulation of endothelin 1 and growth factor receptor-bound protein 2 was identified as a key synergistic mechanism underlying the anti-AMI effects of BBP in STDP. Conclusion This research provides a scientific explanation of the compatibility of BBP in STDP. Our findings suggested that combination treatment with CF and BBP synergistically attenuates AMI by altering gene expression, gut microbiota, and intestinal metabolite profiles. Graphical Abstract